Supply Chain Analysis and Distribution of Cut Flowers at PT. Bromelia Indah - Maharani, Nadiya; Efendi, Darda; Mulyati, Heti (Engineering And Technology Journal, 2024)
The aim of this research is to obtain a broad picture of the cut flower supply chain, cut flower distribution channels that currently exist in the Company. The method used is descriptive analysis using the horticultural product supply chain development method launched by the Asian Productivity Organization (APO), Japan. The method used in this research is a direct interview method with sources who are directly involved in the company's cut flower supply chain, and the data analysis method uses a qualitative descriptive method. There are cut flower distribution channels to the Company, namely: Cut flower farmer groups as suppliers - Companies - Consumers (direct and indirect). Each member of the chain has its own role and function in maintaining the quality of cut flowers. Maintaining the freshness and quality of cut flowers must be carried out from post-harvest by members of the farmer group chain to the company, they can use water directly, or cotton given water to maintain freshness. And cut flowers can extend their life cycle.